Sodyum sakkarin ve sodyum siklamat karışımının dereceli türev spektroskopisi ile simultane tayini - Turak, Fatma (My University, 1993)
SUMMARY Saccharin cyclamate and their salts have been extensively usid as sugar substitutes. These non-caloric substitutes, which exist as combined, are in the ratio of 1 to 10, respectively in commercial preparations. The quantities of sodium saccharin and sodium cyclamate in a mixture have been determined by different methods. But all these methods require either quite long preliminary separation processes or expensive equipment. Derivative spectrophotmetry is very good tool for the fine resolution of spectra. This method can also be used in analytical chemistry to analyse any mixtures. The proposed method is rabid and sensitive. Although the quantity of sodium saccharin in a mixture can be determined with derivative spectrophotmetry, this technic is not appropriate for sodium cyclamate. So, NF XIII (5) method was used to determine the quantity of sodium cyclamate. As a result. It is understood that derivative spectrophotmetry - which is easier in order to execute and sensitive method - can be used in stead of other methods. - which have been used and difficult - to determine the quantity of sodium saccharin ih sweetener tablets. The method given in USP XXII (3) was used in order to compare with proposed method. The chosen derivative degrees and wavelenghts ( 1D, D, 2D,2D, 2D, 229.7 237.7 227.7 231.7 235.7 2D ) showed that is passible to obtain more sensitive outputs 2^0.7 according to the method in USP XXII. The optimum conditions to analyse the sodium cyclamate in thetablets could not be determined. Because the derivative peaks belonging the sodium cyclamate are masked by sodium saccharin. Fqr that reason, the quantity analysis of sodium cyclamate in sweetener tablets was done with the method given in National Formulary XIH (5)
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1993
Keywords: Sodyum sakkarin; Türev spektroskopisi